Aerodynamics of a swirling fluidized bed - Mohd Nawi, Mohd Al-Hafiz (2013)
Swirling Fluidized Bed (SFB) is one of the fluidized bed systems that have potential to be widely used in the mineral processing, power generation and chemical industries. By using an annular bed and inclined injection of gas through the distributor in SFB it will archive a high performance in fluidization. A numerical simulation Computational Fluid Dynamics (CFD) and experimental work with Particle Image Velocimetry (PIV) has been used to investigate physical parameters that influence the type of plenum chamber, the distributor pressure drop and the uniformity of tangential velocity distribution. The study focused on the 60 blades distributor whereby the effect of two horizontal inclinations (12° and 15°) and tangential entry plenum chamber (single, double and triple). Three velocities component were analyzed; tangential velocity, radial velocity and axial velocity. In actual industrial applications, the axial velocity will create fluidization while the tangential velocity provides swirling effect. The presence of radial velocity can be explained as a consequence of centrifugal force generated by the swirling gas. The tangential velocity is the major velocity component in this study and it represents the velocity of the swirling air in the annular region of the bed. The uniformity of tangential velocity distribution and pressure drop is set as performance criteria and has been analyzed with statistical method; mean value, standard deviation & root mean square of difference (RMSD). The most significant finding in simulation configuration is the pressure drop of the distributor blade increased when a triple tangential entry plenum chamber along with horizontal inclination 15° has been applied which then create high tangential velocity. Only parameter for double tangential entry plenum chamber consists with horizontal inclination, 12° has been selected to validate with the PIV result. Comparison of the simulation result (CFD) and experimental data (PIV) are presented, and it is confirmed that good agreement is obtained.